A bat-inspired algorithm for structural optimization - Hasançebi, O.; Teke, T.; Pekcan, O. (Computers & structures, 2013)
•Bat-inspired (BI) search is a recently developed optimization technique.•BI makes use of echolocation behavior of bats in seeking a design space.•A novel algorithm is developed with BI for structural optimization.•Capabilities and potentials of BI are investigated in structural optimization.•Efficiency of the BI algorithm is verified thorough numerical examples. Bat-inspired (BI) search is a recently developed numerical optimization technique that makes use of echolocation behavior of bats in seeking a design space. This study intends to explore capabilities and potentials of this newly developed method in the realm of structural optimization. A novel algorithm is developed that employs basic principles of this method for structural optimization problems specifically. Performance of the proposed algorithm is measured using one benchmark as well as three practical truss structures that are sized for minimum weight subject to stress, stability and displacement constraints according to American Institute of Steel Construction-Allowable Stress Design (AISC-ASD) specification. The numerical results demonstrate efficiency of the proposed algorithm in practical structural optimization.